Hubungan Karakteristik Individu, Frekuensi Angkat dan Angkut terhadap Terjadinya Keluhan Low Back Pain pada Pekerja Pengangkut Beras Gudang Bulog - Silfia Adriani; Miladil Fitra; Asep Irfan; Basuki Ario Seno Irfan; Lindawati Lindawati (Jurnal Kesehatan Lingkungan Mandiri, 2025)
Low Back Pain (LBP) is an occupational health problem commonly experienced by informal sector workers, especially those engaged in heavy lifting and carrying activities with non-ergonomic techniques. Workers at the Bulog Sago Warehouse in Pesisir Selatan Regency are at high risk of experiencing LBP due to manual handling practices without ergonomic training. This study aimed to analyze the relationship between individual characteristics (length of employment), lifting load, lifting technique, and lifting frequency with LBP complaints among rice transport workers. The study used an analytical observational design with a cross-sectional approach, conducted from January to June 2025 involving all 48 workers (total sampling). Data were collected through questionnaires and observation sheets, then analyzed univariately and bivariately using the Chi-Square test with a 95% confidence level. The results showed that 66.7% of workers experienced LBP complaints. There were significant relationships between length of employment (p=0.001), lifting load (p=0.047), lifting technique (p=0.003), and lifting frequency (p=0.027) with the incidence of LBP. It was concluded that individual and ergonomic factors significantly influence LBP complaints. Ergonomic training, workload limitation, job rotation, and the use of lifting aids are recommended to reduce the risk of musculoskeletal disorders.